2015
DOI: 10.1093/ntr/ntv063
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of “Hyping” a Black&Mild Cigarillo

Abstract: Introduction: Cigars remain a widely used tobacco product among adolescent and adult populations. The appeal of a certain type of cigar, the cigarillo, may be enhanced by users' beliefs that their harm potential can be reduced by removing the inner tobacco liner before use (a.k.a. "hyping"). The purpose of this within-subject study was to compare the acute effects of smoking an original cigarillo, a modified ("hyped") cigarillo, and an unlit cigarillo. Methods: Twenty smokers (19 males, 1 female; 19 non-Hispan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
4
17
0
Order By: Relevance
“…The increases in plasma nicotine concentrations we observed in exclusive small cigar and cigarillo smokers are similar to, or lower than, those previously reported for ad libitum use of cigarillos. 10,12,20 One study with ad libitum large cigar smoking also reported similar increases in plasma nicotine concentrations as reported here. 11 …”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The increases in plasma nicotine concentrations we observed in exclusive small cigar and cigarillo smokers are similar to, or lower than, those previously reported for ad libitum use of cigarillos. 10,12,20 One study with ad libitum large cigar smoking also reported similar increases in plasma nicotine concentrations as reported here. 11 …”
Section: Discussionsupporting
confidence: 86%
“…Cigar smoking significantly reduced QSU-B and MNWS scores, as previously reported, 8,10,11 suggesting that cigar smoking confers some benefit for reducing the negative symptoms associated with withdrawal.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations